Museum coolness: Creating the desire to revisit - Loureiro, S. M. C.; Blanco, T. (Tourism Recreation Research, 2023)
Museum coolness may contribute to deepening the relationship between visitors and museums. The current research aims to identify the characteristics most associated with the museum coolness index, and empirically analyse atmospheric cues, authentic pride, and passionate desire to revisit as constructs related to the museum coolness nomological network. The current study used Amazon’s Mechanical Turk to recruit 308 UK adult participants who frequently visit museums. Participants completed a structured questionnaire with the scales of the constructs and the socio-demographic variables. The findings suggest that being considered aesthetic, authentic, energetic, high status, and useful are the most relevant characteristics to form the museum coolness index. The museum’s décor, permanent displays, facilities, and colours are the most important cues appreciated by visitors to consider a museum as cool. As outcomes of museum coolness, the current study empirically demonstrates the role of authentic pride and passionate desire to revisit. Managerial implications and future research are also suggested.